DANA PENSIUN PENDORONG KESEJAHTERAAN PEKERJA DAN PENJAGA EKSISTENSI UMKM DALAM MENGHADAPI MASYARAKAT EKONOMI ASIA - Lokot Zein Nasution; Muhammad Khoirul Fuddin (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
This paper discusses the importance of pension fund which is a non-banking financial institution that has Perana in promoting economic growth and the welfare of workers in the retirement age and its benefits to eksistensu SMEs in the face of the Asean Economic Community (AEC). The purpose of this study to see the importance of the pension fund for workers during the later retirement age and the need for pension funds to the survival of SMEs in the face of the Asean Economic Community (AEC). The results explain that the role of pension funds are expected not just those given priority to the final target is to meet the needs of the current workforce entry age pension which is more widely used in the activities of a consumptive but expected the pension fund can be used not only by the participant retires but family members as well can be used for activities - activities such as setting up operations without having to wait for the parties concerned entered the retirement age. So with demikan welfare pension fund participants and families will be more prosperous and productive. It is then hoped all companies or small-scale industry should have a medium or large and obliging each program tenagakerjanya have pension funds to avoid terjadniya mobilization of human resources to a foreign company at the time of entering the MEA 2015. With the increased prosperity that it offered by domestic perusaaahn one of them by giving progam pensions to workers expected the existence and well-being of the workforce will increase.